2022
DOI: 10.1108/jrme-04-2022-0052
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurs as influencers: the impact of parasocial interactions on communication outcomes

Abstract: Purpose Drawing on the example of car manufacturer Tesla and its early investor Elon Musk, the purpose of this paper is to explore the connection between the personal communication activities of influential entrepreneurs on social media, the emergence of parasocial interactions (PSIs) and the related communication outcomes for the company. Design/methodology/approach This paper conducted an online survey, recruiting 207 participants via purposive sampling. Partial least square path modeling and an independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…The influence of personal communications of influential entrepreneurs on social networks is examined through least squares path modeling and an independent t-test to analyze the results of a sociological survey on the influence of opinion leaders. The results showed that opinion leaders can exert a direct influence on a part of society and form value priorities, which can be used in a fight against discrimination [Rudeloff, C. and Damms, J. (2022)].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The influence of personal communications of influential entrepreneurs on social networks is examined through least squares path modeling and an independent t-test to analyze the results of a sociological survey on the influence of opinion leaders. The results showed that opinion leaders can exert a direct influence on a part of society and form value priorities, which can be used in a fight against discrimination [Rudeloff, C. and Damms, J. (2022)].…”
Section: Literature Reviewmentioning
confidence: 99%